La responsabilité des initiés et le délit d’initié - Monette, Jacques (Assurances)

(untitled) (HEC Montréal, 1988)
Under the Securities Act (Quebec) and the Canada Business Corporations Act, the senior management and the directors of a corporation which has made a public issue or whose shares are listed on the stock market cannot use insider information to their advantage for as long as such information has not been publicly disclosed. According to law, they are considered insiders and may be fiable to heavy penalties if they fail to abide by its provisions. In the following article, the author discusses the duties of insiders.